A large interspersed repeat found in mouse DNA contains a long open reading frame that evolves as if it encodes a protein. - Martin, S L (1984)
DNA sequence analysis of a region contained within a large, interspersed repetitive family of mice reveals a long open reading frame. This sequence extends 978 base pairs between two stop codons, creating a reading frame that is open for 326 amino acids. The DNA sequence in this region is conserved between three distantly related Mus species, as well as between mouse and monkey, in a manner that is characteristic of regions undergoing selection for protein function.